EFFECT OF ORGANIC FERTILIZER, PHOSPHORUS FERTILIZERS SOURCES AND AMOUNTS OF IRRIGATION WATER IN CONTAINT CORN PLANT FROM P - TABAN, SADIK KADHEM; JUBER, ABED SALMAN (Diyala Agricultural Sciences Journal, 2016)
To study impact of organic fertilizer, P sources and irrigation water amounts in content of corn from phosphorus afield experiment was conducted in Agriculture College – University of Baghdad at year 2012 by using three sources of fertilizers phosphate ( triple super phosphate TSP, di ammonium phosphate DAP, urea phosphate UP) at rate 100 kg p.ha-1 and two levels of organic fertilizer (0,1.5 Mg.ha-1) and three levels of irrigation water which were levels 60%,80%,100% of total water requirement by plant (675mm). theresults showed superiority source urea phosphate UP significantly between different sources of phosphorus in P concentrations increased in each of the dry matter and grain , which amounted to 0.27% , 0.67% respectively. Addition of organic fertilizer significantly impact where achieved the highest rate of the concentration of phosphorus in the dry matter and grain amounted to 0.24% , 0.58% respectivly . level W3 (100% of the total water requirement ) achieved the highest rate of concentration of P compared to the levels other , also effected significantly di and tri interaction in the concentrations of P in the dry matter and grain respectivly .